Vancomycin Nephrotoxicity Causing Renal Transplant Acute Kidney Injury - Ngoentra Tantranont (2022)
Nephrotoxicity is a rather frequent side effect of vancomycin treatment. Attributes of vancomycin nephrotoxicity (VN) are well documented, including its clinical manifestations and renal morphologic changes. However, VN has not been emphasized as the cause of acute kidney injury (AKI) in the renal transplant setting. We report the first 3 such cases. In each of these cases, AKI developed concurrently with vancomycin treatment and resolved after its cessation. As compared with the general population, VN in the renal transplant setting displayed some unusual clinical behaviors. Its development was rather capricious, being noted in some but not every episode of vancomycin treatment, even in the same individual. AKI developed gradually in conjunction with protracted vancomycin treatment, in contrast to a precipitous course in the nontransplant setting. However, renal transplant biopsies showed typical features of VN in each case. VN is an unusual but now well-documented cause of AKI in renal transplant recipients. VN in this setting may display some atypical features, setting it apart from that in the general population. However, renal transplant biopsy changes are characteristic and are amenable to a definitive diagnosis.